Defect detection in thermal image using thresholding technique - Heriansyah, Rudi (2007)
This paper proposes a technique to detect defects as depicted in a thermal image. The technique is based on a local neighborhood pixel operation using kernel window 3x3. All pixels within this window will be mapped to only a single pixel value. Next, the thresholding technique is used. The main focus of the employed thresholding technique is the popular Otsu method and testing with other global thresholding technique is also given in the text. From the results obtained, it is shown that the proposed method is able to detect defects occur in a thermal image using any standard thresholding technique which is not designed for thermal images. The technique is easy to implement yet the result is promising.